The Austrian Theory of Business Cycles : Old Lessons for Modern Economic Policy? - Oppers, S. (IMF Working Papers; Working Paper ;, 2002)
This paper reviews the "Austrian" theory of the business cycle first proposed by Friedrich Hayek in the 1920s. His theory claimed that credit creation by monetary authorities would push investment beyond society's long-term willingness to save, creating a mismatch between supply and demand that would inevitably cause recession. The theory argued, moreover, that expansionary policies in recession could generally only postpone the necessary structural adjustment, making the subsequent correction more severe. Modern followers of this theory see Austrian features in a number of recent business cycles, including Japan in the 1980s and 1990s, and the more recent U.S. slowdown.